The effect of applying fair accounting on the quality of financial reports from the auditors' point of view: (A field study for Saudi Telecom Company) - Muhammad, Salwa Dirar Awad (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to measure the effect of applying fair accounting on the quality of financial reports from the auditors 'point of view through knowing the reality of interest in them, and showing the impact of accounting disclosure according to the basis of fair value on the quality of financial reports from the auditors' point of view and the study examined the reality of completion of applying fair accounting in the Saudi business environment. Measuring the impact of accounting disclosure according to fair value on the quality of financial reports. The study used a sample of the auditors at Saudi Telecom Company, where an electronic questionnaire was designed and sent to the sample to clear their opinions on the impact of the application of fair accounting on the quality of the company's financial reports. The number of responses was (52) responses. The researcher used the descriptive analytical approach.The results of the study showed that there is an application of the fair value in the qualitative characteristics of accounting information and this is an indication of the quality of financial reports and that the application by the Saudi fair value companies increases the degree of reliability of the information and the study recommended the need to emphasize Saudi joint stock companies to adhere to the standard of fair value accounting and work to raise the level Coordination and interaction between Saudi universities and academic and training institutions and between joint stock companies that apply accounting standards in order to mix theoretical knowledge with the practical experience of workers in those companies.
Keywords: fair value; auditors; quality of financial reports; disclosure